2008
DOI: 10.1002/pssa.200777765
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial anisotropy of organic thin films determined by ellipsometry

Abstract: Organic thin films frequently exhibit strong anisotropic optical constants, which in many cases are uniaxial with the optic axis oriented along the surface normal. The data analysis presented here to obtain the anisotropic optical constants of thin films on silicon substrates is based on the model system diindenoperylene (DIP), but nevertheless applies to all uniaxial films on SiO2. In addition to variable angle spectroscopic ellipsometry, different substrates are used to perform a multiple sample analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…The morphology and the crystal structure of the active layer is crucially important for the efficiency of organic photovoltaic cells. The orientation of the molecules in the film determines the coupling strength of the transition dipole to the incoming light and hence strongly affects the absorption of the active layer [51,52]. The crystal structure and the defect density in the organic films strongly influence the exciton diffusion length and also the charge transport properties of the films, which are vital for the efficiency of the photovoltaic cell.…”
Section: Interface Morphology and Mixing Behaviourmentioning
confidence: 99%
“…The morphology and the crystal structure of the active layer is crucially important for the efficiency of organic photovoltaic cells. The orientation of the molecules in the film determines the coupling strength of the transition dipole to the incoming light and hence strongly affects the absorption of the active layer [51,52]. The crystal structure and the defect density in the organic films strongly influence the exciton diffusion length and also the charge transport properties of the films, which are vital for the efficiency of the photovoltaic cell.…”
Section: Interface Morphology and Mixing Behaviourmentioning
confidence: 99%
“…As it is known from the literature [36][37][38] VASE data are not very sensitive to uniaxial anisotropy on native oxide which could be confirmed by our own measurements. 31 In order to increase the sensitivity, a multiple sample analysis was performed, where the optical functions for the DIP films on both substrates, Si with native and with thermal oxide, are coupled to be the same. This is a reasonable assumption since both films were grown simultaneously and additional AFM pictures did not show any differences in morphology.…”
Section: ͒ R P R Smentioning
confidence: 99%
“…Besides, Heinemeyer et al (2008) utilized MSA to focus on uniaxial anisotropy of organic thin films, while other research groups have reported optical constants for silicon and thermally grown silicon oxide over the energy range of 0.75-6.5 eV (Herzinger et al, 1998), band gaps for W oxides and Ni oxides (Valyukh et al, 2009) and optical properties evaluation for the fluorocarbon films plasma deposited on silicon substrates (Easwarakhanthan et al, 2007). In this study, we aim to study the morphology of different PMMA thin films with different thicknesses deposited by spin coating on silicon substrates.…”
Section: Introductionmentioning
confidence: 99%